Estimation of reference values of foliar concentration of N, P, K y Ca, adjusted to andean blackberry crops (Rubus glaucus Benth.) in Colombia (2018)
The soils cultivated with andean blackberry in Colombia are fertilized without considering the species nutritionals requirements. Fertilization is carried out without certainty of when applications are required depending of the phenological stage of the established crops. The aim of this study was to estimate the reference values of foliar concentration of N, P, K and Ca for andean blackberry crops in Colombia.